Amil Zakat sebagai Ashnaf; Telaah Fikih dan Implementasinya - Mushlih Candrakusuma; Rudi Purnomo (Universitas Muhammadiyah Jember, 2026)
Amil are the administrators who collect and distribute zakat. In the Qur'an, Allah SWT stipulates eight groups entitled to receive zakat (ashnāf), explicitly listing amil as one of the groups entitled to receive zakat. Some scholars argue that amil must be selected and appointed by a legitimate authority, while others open up the possibility of a wider community role in appointing amil. These differences in interpretation show that the concept of amil as ashnāf is not static, but develops according to social dynamics and the needs of the community. This study uses a normative legal research method with a qualitative descriptive-analytical approach. The data used are secondary, including fiqh books, scientific books, fatwas, and journal articles relevant to the theme of zakat and amil. Data analysis was conducted qualitatively using content analysis techniques. The results of this study are that in the current contemporary era, a paradigm shift in the concept of amil zakat has occurred towards an institutionalization process, where amil is understood as an integrated part of an institutional system regulated through a management science approach, legal mechanisms, organizational structures, financial administration, and public policy. The change in the zakat amil model from a normative understanding to an empirical-applicative one is a form of contextual ijtihad that takes into account the complexity of socio-economic dynamics without sacrificing the basic principles of classical fiqh.